2001
DOI: 10.1159/000049698
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Ligation and Puncture as a Model of Sepsis in the Rat: Influence of the Puncture Size on Mortality, Bacteremia, Endotoxemia and Tumor Necrosis Factor Alpha Levels

Abstract: Background: Cecal ligation and puncture is a widely used experimental model of sepsis. Aim of the Study: The present study was aimed to evaluate the influence of the size of the cecal puncture on mortality, bacteremia, endotoxemia and plasma TNF-α levels. Materials and Methods: Female Sprague-Dawley rats underwent cecal ligation and puncture, divided into the following groups, defined by the diameter of the cecal puncture: 0.5-cm blade incision (n = 25), 13-gauge (n = 25), 16-gauge (n = 25), 18-gauge puncture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 4 publications
7
74
0
3
Order By: Relevance
“…In present study, similar results were found as pus pocket formation and pus over caecum were more in rats who had larger caecal perforation. Caecal perforation size also seems to influence the systemic toxemia produced in peritonitis as proved by E. 8 The subjects were re-explored on the fifth day. This allowed enough time for the rats to come out of immediate postoperative stress and helped us to observe the short term results of the experimental drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study, similar results were found as pus pocket formation and pus over caecum were more in rats who had larger caecal perforation. Caecal perforation size also seems to influence the systemic toxemia produced in peritonitis as proved by E. 8 The subjects were re-explored on the fifth day. This allowed enough time for the rats to come out of immediate postoperative stress and helped us to observe the short term results of the experimental drugs.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The organ dysfunction which is caused by peritonitis is worsened by free oxygen radicals those are the result of endotoxic shock. 6,7,8 The Caecal Ligation and Puncture (CLP) technique of peritonitis model in albino rats is good, economical and easily reproducible in experimental model for evaluation of new treatment modality. 9 The present study was carried out to assess the effect of intra-peritoneal Vitamin E and Metronidazole either singly or in combination, in experimentally produced faecal peritonitis model.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis was induced by the CLP model which was performed beforehand in different researches (13,14). After the administration of anesthesia under septic conditions, a 2 cm midline incision was made.…”
Section: Constitution Of Sepsis Modelmentioning
confidence: 99%
“…Septik cevapta fizyopatolojik olaylar oldukça karmafl›k olmas›na ra¤men moleküler biyoloji alan›ndaki geliflmeler, sepsiste oluflan patolojik olaylar›n bir ço¤unun anlafl›lmas›n› mümkün k›lm›flt›r. Sepsiste ortaya ç›kan serbest oksijen radikalleri DNA'da hasara, hücresel proteinlerde denaturasyona ve membran lipitlerinde peroksidasyona yol açarak doku hasar›na neden olur (3,4) . Yap›lan çal›flmalarda sepsisde ortaya ç›kan serbest oksijen radikallerinin etkilerini nötralize etmek için uygulanan antioksidan ajanlar›n kullan›m›n sa¤ kal›m› uzatt›¤› gösterilmifltir (5) .…”
Section: G‹r‹fiunclassified
“…Çal›flmam›zda, deneysel sepsis modeli oluflturarak sentetik bir antioksidan ajan olan NAC ile antioksidan özelli¤ine ilaveten antibakteriyel özelli¤i bulunan Erdostein'i, doku hasar›na sebep olan veya fliddetini artt›ran mekanizmalara karfl› antioksidan tedavinin etkinlikleri aç›s›ndan karfl›laflt›rd›k. (9) . Laparotomi sonras› çekum izole edilerek, ç›kan kolon s›vazlanarak, çekum gaita ile doldurulduktan sonra ileoçekal valvin alt›ndan 3/0 ipek ile ba¤lan›p, çekum ön yüzü 18 numara intraket i¤nesi ile iki defa delindi.…”
Section: G‹r‹fiunclassified